The Relationship Between Social Intelligence and Anchoring Bias in Young People A Field Study of Sociology Students at the Universities of Damascus and Latakia (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This study aimed to examine the relationship between social intelligence and anchoring bias among students in the Department of Sociology at Damascus University and Latakia University. To achieve this objective, the study employed the analytical descriptive approach and used the social survey method with a sample. The study utilized a social intelligence scale and an anchoring bias scale, and it was administered to a sample of 358 male and female students from the two universities.he results of the study showed that there was a statistically significant negative relationship between social intelligence and anchoring bias. This indicates that students with higher levels of social intelligence tend to exhibit lower anchoring bias when making decisions. The findings also revealed that the level of social intelligence among the study participants was moderate (average). Furthermore, the results indicated that students in the research sample tend to rely on initial information when making decisions.As the results indicate, the place of residence had a significant impact on levels of social intelligence and anchoring bias, as students from rural areas demonstrated better social interaction skills.
Keywords: Anchoring bias, anchoring, cognitive biases, social intelligence, university students.